Strengthening Sustainable Water Management in Coastal Polders of Bangladesh: Importance of Institutional and Policy Reform - Salahuddin, Ahmad; Amin, Md. Ruhul; Humaira, Bushra (International Rice Research Institute, 2025)
The coastal region of Bangladesh, encompassing 19 districts and approximately 30% of national land, relies on 139 polders covering 1.2 million hectares to protect communities and agriculture from flooding and salinity intrusion. Despite these engineering structures, outdated infrastructure, weak institutional arrangements, and poor policy enforcement have reduced the effectiveness of water management systems, increasing vulnerability to climate change impacts such as waterlogging, salinity, drought, and sea-level rise. This factsheet emphasizes the need for strengthening Water Management Organizations (WMOs), establishing clear lead agencies, and integrating participatory approaches for sustainable polder management. Recommendations include empowering WMOs, using polders and sub-catchments as planning units, leveraging engineering support from BWDB and complementary roles of LGED, BADC, and DAE/DoF, and adopting innovative approaches such as CS-MAP for adaptive water management planning. Implementation of these recommendations is expected to enhance agricultural productivity, climate resilience, cropping intensity, and integrated polder development.